Biosynthesis of the Nematode Attractant 2-Heptanone and Its Co-evolution Between the Pathogenic Bacterium Bacillus nematocida and Non-pathogenic Bacterium Bacillus subtilis - Zhu, Man; Xu, Xiao’e; Li, Yuhong; Wang, Pengfei; Niu, Shanzhuang; Zhang, Keqin; Huang, Xiaowei (Frontiers in Microbiology, 2019)
Methylketones are broadly distributed in nature and perform a variety of functions. Most microorganisms are thought to produce methylketone by abortive β-oxidation of fatty acid catalytic metabolism. However, two methylketone synthetase genes in wild tomatoes are reported to synthesize methylketone using intermediates of the fatty acids biosynthetic pathway. In our previous study on Trojan horse-like interactions between the bacterium Bacillus nematocida B16 and its host worm, the chemical 2-heptanone was found to be an important attractant for the hosts. So here we used this model to investigate the genes involved in synthesizing 2-heptanone in microorganisms. We identified a novel methylketone synthase gene yneP in B. nematocida B16 and found enhancement of de novo fatty acid synthesis during 2-heptanone production. Interestingly, a homolog of yneP’ existed in the non-pathogenic species Bacillus subtilis 168, a close relative of B. nematocida B16 that was unable to lure worms, but GC-MS assay showed no 2-heptanone production. However, overexpression of yneP’ from B. subtilis in both heterologous and homologous systems demonstrated that it was not a pseudogene. The transcriptional analysis between those two genes had few differences under the same conditions. It was further shown that the failure to detect 2-heptanone in B. subtilis 168 was at least partly due to its conversion into 6-methyl-2-heptanone by methylation. Our study revealed methylketone biosynthesis of Bacillus species, and provided a co-evolution paradigm of second metabolites during the interactions between pathogenic/non-pathogenic bacteria and host.